Muscle Activity while Standing for Prolonged Time Periods in Metal Stamping Industry - Isa, Halim; Al Amin, Mohamed Sultan; Seri Rahayu , Kamat; Rohana, Abdullah (2012)
In metal stamping industry, many tasks require workers to perform in standing position. Standing is a practical working position when the workers are lifting heavy products, reaching materials, and pushing or pulling excessive loads because those tasks require a stable position and large degree of freedom. However, if the workers perform the tasks continuously in standing throughout the working hours, they may be experience muscle fatigue. The objective of this study is to measure the myoelectric levels (μV) exerted by the left and right erector spinae, left and right tibialis anterior, and left and right gastrocnemius muscles while workers perform metal stamping process and hand grinding processes in a metal stamping industry. The myoelectric levels in the muscles were measured using surface Electromyography (sEMG). Ten production workers from a metal stamping industry participated as subjects for sEMG measurement. Out of which, five workers from metal stamping process lines and another five from handwork section. The muscle activity of the subjects was measured for 5 hours and 45 minutes of continuous standing during beginning of workday, middle of workday, and end of workday from Monday to Wednesday. Results of comparison found that the two groups of workers show significant difference (p-value < 0.05) in myoelectric level in the right erector spinae, right gastrocnemius, and left tibialis anterior during the beginning of workday. However, the two groups of workers did not show any significant difference in myoelectric level during the middle of the workday and end of the workday. Based on this study, the authors concluded that muscle activity of the workers was determined by the work load and duration of standing.